Identification of Bioactive Components from Ruellia tuberosa L. on Improving Glucose Uptake in TNF-α-Induced Insulin-Resistant Mouse FL83B Hepatocytes. (1st December 2020) - Xu, Jian-Hua; Lo, Yangming Martin; Chang, Wen-Chang; Huang, Da-Wei; Wu, James Swi-Bea; Jhang, Yu-Yuan; Huang, Wen-Chung; Ko, Chih-Yuan; Shen, Szu-Chuan
Abstract : Ruellia tuberosa L. (RTL) has been used as a folk medicine to cure diabetes in Asia. RTL was previously reported to alleviate hyperglycemia, insulin resistance (IR), abnormal hepatic detoxification, and liver steatosis. However, the potential bioactive compounds of RTL have still not been identified. The aim of this study was to investigate the bioactive compounds in RTL ethyl acetate (EA) fractions by using a glucose uptake assay in TNF- α -treated mouse FL83B hepatocytes to discover a mechanism by which to improve IR. The bioactive compounds were identified by the high-performance liquid chromatography (HPLC) assay. Using the Sephadex LH20 gel packing chromatography column, the EAF5 fraction was isolated from RTL and significantly increased glucose uptake in TNF- α -treated FL83B cells. Moreover, the MCI gel packing chromatography column separated EAF5 into five subfractions and had no significant cytotoxic effect in FL83B cells when treated at the concentration of 25  μ g/ml. Among the subfractions, EAF5-5 markedly enhanced glucose uptake in TNF- α -treated FL83B cells. The possible bioactive compounds of the EAF5-5 fraction that were identified by the HPLC assay include syringic acid, p -coumaric acid, and cirsimaritin. The bioactive compound with the best effect of increasing glucose uptake was p -coumaric acid, but its effect alone was not as good as the combined effect of all three compounds of the EAF5-5 fraction. Thus, we speculate that the antidiabetic effect of RTL may be the result of multiple active ingredients.